Parallel Imports of Pharmaceutical Products in the European Union - Mattias Ganslandt; Keith E. Maskus (The Research Institute of Industrial Economics (IUI), 2001)
We study the effects of parallel trade in the pharmaceutical industry. We develop a model in which an original manufacturer competes in its home market with parallel-importing firms. The theoretical analysis results in two key hypotheses. First, if the potential for parallel imports is unlimited, the manufacturer chooses deterrence and international prices converge. Second, with endogenously limited arbitrage the manufacturing firm accommodates and the price in the home market falls as the volume of parallel trade rises. Simple empirical tests favor the accommodation hypothesis with a time lag. Using data from Sweden we find that the prices of drugs subject to competition from parallel imports increased less than other drugs during the period 1995-1998. Approximately 3/4 of this effect on be attributed to lower prices of parallel imports and 1/4 to lower prices charged by the manufacturing firm. Econometric analysis find that rents to parallel importers (or resource costs in parallel trade) could be more than the gain to consumers from lower prices.
Keywords: F12; I11; L12; 330; Parallel Imports; International Arbitrage; Drug Pricing; Pharmazeutisches Produkt; Import; EU-Staaten; Grauer Markt